Inoculation of indole-3-acetic acid producing bacteria in lettuce (Lactuca sativa L.) plants - Florentino, Ligiane A.; Silva, Adriano B.; Landgraf, Paulo R. C.; Souza, Flávia R. C. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
Microorganisms are of great importance for the development of plants through the production of various compounds, such as indole-3-acetic acid (IAA), synthesized by bacteria. However, research on the effect of inoculation of these bacteria on plants is still lacking. The objective of this study was to evaluate the in vitro production of IAA by diazotrophic bacteria grown in the presence or absence of tryptophan (Trp) and the effect of inoculation of these strains on lettuce seeds (Lactuca sativa L.). Initially, a completely randomized design experiment (DIC) was installed in a 19 × 2 factorial scheme, with 19 bacterial strains grown in media containing or not containing Trp, with four replications. It has been observed that Trp contributes to a higher production of IAA by most strains. Subsequently, six of these strains were selected for inoculation in lettuce seeds in two experiments: the first in gerbox and the other in trays containing commercial substrate. DIC was used in a 8 × 2 factorial scheme, with seven bacterial strains and one control without inoculation and the presence or absence of Trp in the culture medium, with four replications. Inoculation with most of the strains contributed to an increase in the seed germination rate, root length and shoot dry matter weight; however, the excess of IAA produced by some strains when grown in the presence of Trp may interfere with the development of lettuce seedlings.